Have hospital readmissions increased in the face of reductions in length of stay? Evidence from England. Issue 1 (January 2016) - Martin, Stephen; Street, Andrew; Han, Lu; Hutton, John
Highlights: There is no definitive evidence about the relationship between hospital length of stay and subsequent readmission. Studies exploring the relationship have not conditioned on the probability of surviving the first admission. We analyse length of stay, in-hospital mortality and 28-day readmission for three conditions in England over 7 years. Stroke patients with shorter LoS were more likely to be readmitted, and the probability was unchanged as LoS fell over time. For hip replacement and hernia repair, length of stay was not associated with an increased probability of readmission. Abstract: We assess the relationship between changes in hospital length of stay (LoS) and hospital quality, as measured by 28-day emergency readmission. We estimate regression models to analyse LoS and other factors associated with readmission for all those admitted for hip replacement ( n = 496, 334), hernia repair ( n = 413, 712) or following a stroke ( n = 480, 113) in England between 2002/3 and 2007/8. There were reductions in LoS over time while changes in crude readmission rates varied by condition. Given the high mortality rate for stroke, it is critical to account for the probability of surviving the initial admission when evaluating readmissions. Conditional upon survival, the probability of readmission was greater for stroke patients who originally had a shorter LoS and for hernia patients who had an overnight stay but there is no relationship between LoS and readmission for patients who had hip replacement. The evidence does not generally suggest that reductions in LoS were associated with an increased probability of emergency readmission.